2012
DOI: 10.1097/prs.0b013e318244222d
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Recognizing and Managing Intraoperative Venous Congestion in Abdominally Based Autologous Breast Reconstruction

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 48 publications
2
62
0
2
Order By: Relevance
“…Other common strategies include the anastomosis of the SIEV to a second internal mammary vein, to an internal mammary perforator, or end-to-side to one of the DIEVs of the flap. [10,25,26] Less popular options include the anastomosis of the SIEV to the thoracoacromial vein, to the contralateral intermammary vein (which may need a vein graft), or to the toracodorsal vein (which may prevent the use of a latissimus dorsi as a rescue surgery in case the DIEP flap fails), among others. Notwithstanding, carrying out a second venous anastomosis is timeconsuming, which represents the main drawback of this procedure, taking between 30 to 90 min.…”
Section: Taking Into Account the Redirection Of The Venousmentioning
confidence: 99%
See 1 more Smart Citation
“…Other common strategies include the anastomosis of the SIEV to a second internal mammary vein, to an internal mammary perforator, or end-to-side to one of the DIEVs of the flap. [10,25,26] Less popular options include the anastomosis of the SIEV to the thoracoacromial vein, to the contralateral intermammary vein (which may need a vein graft), or to the toracodorsal vein (which may prevent the use of a latissimus dorsi as a rescue surgery in case the DIEP flap fails), among others. Notwithstanding, carrying out a second venous anastomosis is timeconsuming, which represents the main drawback of this procedure, taking between 30 to 90 min.…”
Section: Taking Into Account the Redirection Of The Venousmentioning
confidence: 99%
“…[10][11][12] However, the origin remains to be elucidated. Some triggering factors have been proposed: diameter of the SIEV larger than 1.5 mm, [6,13] absence of communications of both SIEVs crossing the abdominal midline, [6,13] absence of direct communications by perforators between the SIEV and the deep inferior epigastric vein (DIEV), [6] number of perforators of the flap, [5] and subcutaneous tissue thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Anatomic studies have shown that the deep inferior epigastric vein (DIEV) connects with the superficial inferior epigastric vein (SIEV) through a system of choke vessels within the flap. [8] In numerous studies, the superficial venous system has been used to adequately decongest the flap in cases where venous congestion was clinically observed [9][10][11][12][13]. We have found that routinely anastomosing both the superficial and deep venous systems has resulted in significantly fewer operative take-backs and decreased venous complications with use of the DIEP flap.…”
Section: Introductionmentioning
confidence: 81%
“…The main causes of venous congestion are venous thrombosis, inadequate venous drainage, inadequate perforator selection, and anatomic superficial venous system dominance with insufficient communicating veins to the deep system [4][5][6]. In contrast, cold urticaria prevalence is not well determined and has an estimated incidence rate of 0.05% [3].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of venous congestion status in DIEP and transverse rectus abdominis myocutaneous flaps for breast reconstruction is not rare, ranging from 2 to 20% [4][5][6]. The main causes of venous congestion are venous thrombosis, inadequate venous drainage, inadequate perforator selection, and anatomic superficial venous system dominance with insufficient communicating veins to the deep system [4][5][6].…”
Section: Discussionmentioning
confidence: 99%